Analisis Dan Penerapan Standar Biaya Produksi Sebagai Pengendalian Biaya Bahan Baku, Biaya Tenaga Kerja Langsung, Biaya Overhead Pabrik - Claudia Nikiletta; Lis Lestari Sukartiningsih (Akubis : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to analyze and establish production cost standards as raw material cost control, direct labor costs, factory overhead costs at Winston Candy Company PT Madukara Malang. Methods of data collection through field studies and literature studies with data collection techniques of observation, interviews, and documentation. Data analysis used quantitative descriptive. The problem faced by the company in 2020 is that production costs are not optimal, as evidence of the realization of spending on raw material costs, labor costs, factory overhead costs with the budget prepared by the company. The cause of the problem is that the company does not make standard costs that match the actual costs, resulting in the company getting a loss. The results of the quantitative descriptive analysis, the company can find out the amount of difference in raw material costs, labor costs, and factory overhead costs. Avoiding loss of cost differences The company sets standard raw material costs, labor costs and factory overhead using the least square method for 2023